1993
DOI: 10.1161/01.atv.13.10.1487
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of body fatness and body fat distribution on risk factor for cardiovascular disease in women. Impact of weight loss.

Abstract: This study examines the role of obesity and body fat distribution (ie, waist-to-hip ratio [WHR]) on cardiovascular disease (CVD) risk factors in 50 nondiabetic, obese (body mass index [BMI], 31±2 kg/m 2 , mean±SD), 45±10-year-old women. The data obtained at baseline and after weight loss were analyzed after dividing subjects by WHR into upper-body (WHR >0.80) and lower-body (WHR £0.80) groups and by median-split BMI into more obese (BMI s31) and less obese (BMI <31) groups. At baseline, the upper-body obese wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
(17 reference statements)
2
14
0
Order By: Relevance
“…It is evident from a comparison of our data with those previously reported [27,52] that WHR is a more effective predictor for the patterns of lipid and glucose metabolism than CHR, but the latter index has the more predictive power for the morning cortisol compared with the first one. On the other hand, HPA axis responsiveness to stress and pharmacological stimulation or suppression depends on WHR [14].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…It is evident from a comparison of our data with those previously reported [27,52] that WHR is a more effective predictor for the patterns of lipid and glucose metabolism than CHR, but the latter index has the more predictive power for the morning cortisol compared with the first one. On the other hand, HPA axis responsiveness to stress and pharmacological stimulation or suppression depends on WHR [14].…”
Section: Discussionsupporting
confidence: 69%
“…There was previously described a predominant reduction in waist circumference when compared with hip after WLP for women with abdominal BFD but not for those with gluteofemoral BFD [52]. These findings were confirmed by the in vitro biochemical investigations of glucose and lipid metabolism patterns in human adipocytes from abdominal and gluteal regions [53].…”
Section: Discussionsupporting
confidence: 60%
“…It has recently been shown that con sumption of a low-fat diet induces a decrease of plasma cholesterol concentrations when ac companied by loss of body weight [15]. Fur thermore, Dattilo [16] and Dennis [17] have shown that body weight reduction was associ ated with a decrease of plasma total cholester ol, LDL cholesterol, VLDL cholesterol and triglycerides, and an increase in HDL choles terol. These data are in agreement with our results which showed that during Ramadan fasting, the fall in serum cholesterol and tri glycerides is accompanied by a loss of body weight when analyzed by paired data.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Weight loss has bene®cial effects on other risk factors as well. 5,6 During weight loss with a very-low-calorie diet (VLCD), a rapid decrease in BP, both in hypertensive and normotensive, obese subjects has been reported previously, 7,8 and this seems to be independent of sodium intake. 7 The role of sodium restriction on BP during less severe energy restriction is controversial.…”
Section: Introductionmentioning
confidence: 87%